2019
DOI: 10.1111/are.14300
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive recording of brain function in rainbow trout: Evaluations of the effects of MS‐222 anaesthesia induction

Abstract: Effective methods of producing instantaneous and irreversible unconsciousness at the time of slaughter are crucial for ensuring animal welfare in commercial aquaculture. However, the traditional method of visually evaluating unconsciousness has been shown to be insufficient and may lead to misjudgements of stunning efficiency. In this study, we developed a non‐invasive technique that measures brain activity in fish as an alternative to traditional invasive, brain implants and used it to determine when a change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Previous studies have shown that loss of VERs indicates a degree of brain failure indicative of insensibility in fish (Bowman et al., 2019; Bullock, Hofmann, New, & Nahm, 1991; Kestin et al., 1991, 1995; Readman, 2015; Retter et al., 2018; Robb & Roth, 2003; Robb et al., 2000; van de Vis et al., 2003), chickens and ducks (Gregory & Wotton, 1986) and livestock (Verhoeven, Gerritzen, Hellebrekers, & Kemp, 2014). While visual indicators of a loss of consciousness in fish are susceptible to misinterpretation from subjective visual observation, the use of EEG to assess VERs allows for a more definitive method of determining when sensibility is lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that loss of VERs indicates a degree of brain failure indicative of insensibility in fish (Bowman et al., 2019; Bullock, Hofmann, New, & Nahm, 1991; Kestin et al., 1991, 1995; Readman, 2015; Retter et al., 2018; Robb & Roth, 2003; Robb et al., 2000; van de Vis et al., 2003), chickens and ducks (Gregory & Wotton, 1986) and livestock (Verhoeven, Gerritzen, Hellebrekers, & Kemp, 2014). While visual indicators of a loss of consciousness in fish are susceptible to misinterpretation from subjective visual observation, the use of EEG to assess VERs allows for a more definitive method of determining when sensibility is lost.…”
Section: Discussionmentioning
confidence: 99%
“…EEG is a method for recording and measuring the electrical activity of the brain through the use of electrodes that are either surgically implanted in the brain (Kestin et al., 2002; Kestin, Wotton, & Gregory, 1991; Quick & Laming, 1990), or attached externally to the head (Bowman, Hjelmstedt, & Gräns, 2019; Cho et al., 2017). EEG allows the investigator to detect changes in brain activity indicative of a loss of consciousness and/or sensibility.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity in capturing neuronal signals and the different monoterpene mechanisms of action, these compounds can elicit different EEG responses. Despite the recent advances in research relating the effects of various compounds on the fish brain activity [1,2,[25][26][27], no studies are available to date, for instance, on the frequency bands and their correlation with general anaesthesia in fish. These are future research arenas that should be explored to best clarify how the fish brain responds to general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore imperative that we continue to research teleost brain region function in commercially relevant lineages. Second, electroencephalography (EEG) has been used to assess brain electrical activity in fish in a number of laboratory experiments and has been shown to be one of the most reliable methods of assessing consciousness [e.g., (162,165,(170)(171)(172)(173)]. However, in a commercial fish farm setting, registration of EEGs is impossible to perform, instead forcing farmers to rely exclusively on behavioral indicators to evaluate the degree of consciousness in fish [e.g., coordinated swimming and escape behaviors, ability to maintain equilibrium, "eye roll" reflex, and ventilatory reflexes; (170)].…”
Section: Slaughter and Euthanasiamentioning
confidence: 99%